2017
DOI: 10.1111/jssr.12349
|View full text |Cite
|
Sign up to set email alerts
|

Religion in Public Health‐Care Institutions: U.S. and U.K. Perspectives

Abstract: In this article, we consider the role that religion plays in the health‐care institutions of the United States and the United Kingdom. Religion has played a significant role in the development of health‐care institutions in both countries and continues to be present in them in important ways. To capture the range of involvement of religious groups in various sectors of the health‐care institution, we propose a continuum for their relationship, from completely merged identities at one end (“faith‐saturated”) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Religion further influences the social and economic systems that generate conditions for health and illness (Milstein et al 2020 ; VanderWeele 2017 ). Most of the recent studies have indicated a positive relationship between various aspects of religion and various aspects of health promotion and disease prevention (Krause 2016 ; Levin 2016 ; Idler and Kellehear 2017 ; Shapiro 2018 ). Many studies refer specifically to the role of social capital elements that are embedded in religion, in the promotion of health, while emphasizing the role of clergy, religious institutions, religious affiliations, inter-communal welfare, and networking, in promoting health behaviors and improving health amongst religious believers (Elgar et al 2017 ; Eriksson 2011 ; Milstein et al 2020 ; Satariano 2020 ; Shapiro and Chen 2018 ).…”
Section: The Link Between Various Aspects Of Religion and Health And Illnessmentioning
confidence: 99%
“…Religion further influences the social and economic systems that generate conditions for health and illness (Milstein et al 2020 ; VanderWeele 2017 ). Most of the recent studies have indicated a positive relationship between various aspects of religion and various aspects of health promotion and disease prevention (Krause 2016 ; Levin 2016 ; Idler and Kellehear 2017 ; Shapiro 2018 ). Many studies refer specifically to the role of social capital elements that are embedded in religion, in the promotion of health, while emphasizing the role of clergy, religious institutions, religious affiliations, inter-communal welfare, and networking, in promoting health behaviors and improving health amongst religious believers (Elgar et al 2017 ; Eriksson 2011 ; Milstein et al 2020 ; Satariano 2020 ; Shapiro and Chen 2018 ).…”
Section: The Link Between Various Aspects Of Religion and Health And Illnessmentioning
confidence: 99%
“…This means that these denominations are full partners in the effort to face the challenge of the current outbreak, and are invested in this work as a central feature of their ministries of service. These faith-based health care partnerships can be instrumental in managing the surge of cases, in meeting the requisite supply chain needs for equipment, and in providing experienced leadership for local community response efforts and even for global outreach (Idler and Kellehear 2017).…”
Section: Religion As Part Of the Solutionmentioning
confidence: 99%
“…One taxonomy differentiates faith-saturated, faith-centered, faithbackground, and other institutional arrangements. 13 These arrangements refer to distinctive ways that religious people and organizations can ally with health care institutions. The key takeaway is that collaborative partnerships of myriad types can be observed between FBOs and the public health sector, with varying levels of institutional autonomy.…”
mentioning
confidence: 99%